Global Daytime Mean Shortwave Flux Consistency Under Varying EPIC Viewing Geometries - Su, Wenying; Liang, Lusheng; Duda, David P.; Khlopenkov, Konstantin; Thieman, Mandana M. (Frontiers in Remote Sensing, 2021)
One of the most crucial tasks of measuring top-of-atmosphere (TOA) radiative flux is to understand the relationships between radiances and fluxes, particularly for the reflected shortwave (SW) fluxes. The radiance-to-flux conversion is accomplished by constructing angular distribution models (ADMs). This conversion depends on solar-viewing geometries as well as the scene types within the field of view. To date, the most comprehensive observation-based ADMs are developed using the Clouds and the Earth's Radiant Energy System (CERES) observations. These ADMs are used to derive TOA SW fluxes from CERES and other Earth radiation budget instruments which observe the Earth mostly from side-scattering angles. The Earth Polychromatic Imaging Camera (EPIC) onboard Deep Space Climate Observatory observes the Earth at the Lagrange-1 point in the near-backscattering directions and offers a testbed for the CERES ADMs. As the EPIC relative azimuth angles change from 168° to 178°, the global daytime mean SW radiances can increase by as much as 10% though no notable cloud changes are observed. The global daytime mean SW fluxes derived after considering the radiance anisotropies at relative azimuth angles of 168° and 178° show much smaller differences (< 1%), indicating increases in EPIC SW radiances are due mostly to changes in viewing geometries. Furthermore, global daytime mean SW fluxes from EPIC agree with the CERES equivalents to within 1.3 Wm-2 with root-mean-square errors less than 2.7 Wm-2. Consistency between SW fluxes from EPIC and CERES inverted from very different viewing geometries indicates that the CERES ADMs accurately quantify the radiance anisotropy and can be used for flux inversion from different viewing perspectives.